2020
DOI: 10.3389/fpsyg.2020.01010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Temporal Lobe Epilepsy and Posttraumatic Stress Disorder: Network Analysis of a Single Case

Abstract: In this case study, we present a 21 years old female with long-standing Temporal Lobe Epilepsy (TLE) who, following a sexual assault, also developed Posttraumatic Stress Disorder (PTSD), leading to a change in her seizure semiology. The new seizures seemed to be a re-enactment of the sexual assault and accordingly were at first thought to be Psychogenic Non-Epileptic Seizures (PNES). Nevertheless, electroencephalography (EEG) recording at the Epilepsy Monitoring Unit (EMU) revealed ictal epileptic brain activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An electroencephalogram is an important method for diagnosing epilepsy and evaluating the effectiveness of treatment ( 43 , 44 ). This study showed that patients with abnormal electroencephalogram findings had a higher SPB than those with normal electroencephalogram findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An electroencephalogram is an important method for diagnosing epilepsy and evaluating the effectiveness of treatment ( 43 , 44 ). This study showed that patients with abnormal electroencephalogram findings had a higher SPB than those with normal electroencephalogram findings.…”
Section: Discussionmentioning
confidence: 99%
“…The more types of medicines taken, the greater the physical, psychological and economic burden of the patient, and the higher the SPB. An electroencephalogram is an important method for diagnosing epilepsy and evaluating the effectiveness of treatment (43,44). This study showed that patients with abnormal electroencephalogram findings had a higher SPB than those with normal electroencephalogram findings.…”
Section: Scatterplot Of Spbs Versus Qolie-(n= )mentioning
confidence: 93%
“…They also reported experiencing more intrusions (thoughts or memories) during the seizure itself (ictal period) than patients without PTSD symptoms. In this way, some case reports have mentioned that epilepsy patients with severe PTSD may have a specific seizure semiology, in that re-experiencing of a traumatic memory may occur during the ictal period [38,39]. These findings presuppose an interaction within limbic networks, particularly involving amygdala hyperactivity that characterizes traumatic memory and epileptogenic networks [22,38,39].…”
Section: 3ptsd Symptoms Specific To Epilepsymentioning
confidence: 99%
“…In this way, some case reports have mentioned that epilepsy patients with severe PTSD may have a specific seizure semiology, in that re-experiencing of a traumatic memory may occur during the ictal period [38,39]. These findings presuppose an interaction within limbic networks, particularly involving amygdala hyperactivity that characterizes traumatic memory and epileptogenic networks [22,38,39]. Repeated exposure to seizures can act as a reinforcer of PTSD according to a mechanism similar to fear conditioning, one major axis of neurobiological theories of PTSD [40].…”
Section: 3ptsd Symptoms Specific To Epilepsymentioning
confidence: 99%